Laboratory selection of Aedes aegypti field populations with the organophosphate malathion: Negative impacts on resistance to deltamethrin and to the organophosphate temephos. - Priscila Fernandes Viana-Medeiros; Diogo Fernandes Bellinato; Denise Valle (Public Library of Science (PLoS), 2018)
BACKGROUND:Resistance to pyrethroids and to the organophosphate temephos is widespread in Brazilian populations of the dengue vector, Aedes aegypti. Thereof, since 2009 Insect Growth Regulators are employed as larvicides, and malathion is used against adults. METHODOLOGY/PRINCIPAL FINDINGS:We performed laboratory selection with malathion of two A. aegypti field populations initially susceptible to this organophosphate but resistant to temephos and deltamethrin. A fixed malathion dose inducing at least 80% mortality in the first generation, was used throughout the selection process, interrupted after five generations, when the threshold of 20% mortality was reached. For each population, three experimental and two control groups, not exposed to insecticides, were kept independently. For both populations, quantitative bioassays revealed, in the selected groups, acquisition of resistance to malathion and negative impact of malathion selection on deltamethrin and temephos resistance levels. In the control groups resistance to all evaluated insecticides decreased except, unexpectedly, to deltamethrin. Analysis of the main resistance mechanisms employed routine methodologies: biochemical and molecular assays for, respectively, metabolic resistance and quantification of the NaV pyrethroid target main kdr mutations at positions 1016 and 1534. No diagnostic alteration could be specifically correlated with malathion selection, neither with the unusual deltamethrin increase in resistance levels observed in the control groups. CONCLUSIONS/SIGNIFICANCE:Our results confirm the multifactorial character of insecticide resistance and point to the need of high throughput methodologies and to the study of additional field vector populations in order to unravel resistance mechanisms.